Dose-Response Effects of Acute Aerobic Exercise Duration on Cognitive Function in Patients With Breast Cancer: A Randomized Crossover Trial - Salerno, Elizabeth A.; Rowland, Kendrith; Hillman, Charles H.; Trinh, Linda; Kramer, Arthur F.; McAuley, Edward (Frontiers in Psychology, 2020)
Objective: To examine the differential effects of acute exercise duration on domains of executive function and processing speed in patients with breast cancer. Methods: Participants (N=48, Mage=56.02±10.99) completed two sessions in counterbalanced order: moderate-intensity treadmill walking and sitting. Participants were also randomized to one of three duration conditions: 10 (n=15), 20 (n=16), or 30 (n=17) minutes, reflecting the length of time spent walking and sitting. Immediately before and after each session, women completed a battery of cognitive tasks (e.g., inhibition, cognitive flexibility, spatial working memory, processing speed). Results: Within- and between-subjects repeated measures analyses of variance revealed time by condition interactions on both processing speed (p=.02) and spatial working memory (ps<.07), such that women demonstrated improved cognitive functioning regardless of the time spent walking. There were also several moderately-sized three-way (e.g., time by condition by duration) interactions, driven by declines in cognitive functioning after sitting on cognitive flexibility in the 10- (d = -.96) and 30-minute (d = -.52) groups and inhibition in the 20-minute group (d = .75). On the processing speed task, women performed significantly faster after walking compared with after sitting in the 20-minute group (d = -.24). Conclusions: For select cognitive domains, walking anywhere from 10 to 30 minutes is associated with significant benefits. Our findings suggest the need for further research into the mechanisms and dose-response relationships between acute exercise and cognition, as well as how such acute bouts may be accumulated for larger, lasting cognitive benefits after breast cancer.